Interactive E-Module Based on Ethnomathematics Upakara Bali in Geometry Subject for 2nd Grade Elementary School - Mahardika, Ni Luh Putu Divya Jyoti; Suarjana, I Made; Werang, Basilius Redan (MIMBAR PGSD Undiksha, 2024)
Mathematics is considered a difficult subject. So in the learning process teachers need teaching materials to help students with difficulties in understanding abstract material. The aim of this research is to create an interactive e-module based on ethnomathematics in mathematics subjects with valid and practical geometry material. The type of research used is development research with the ADDIE model. The test subjects in this research were two material expert lecturers, two media expert lecturers, a class II teacher and 10 students. The data collection method is a questionnaire in the form of a rating scale. The data analysis method uses qualitative and quantitative analysis. Based on the analysis results, it was found that the validity test results according to media experts obtained a score percentage of 99% with very good qualifications. The test results from the teacher's responses obtained a score percentage of 98% with very good qualifications. The test results from individual student trials obtained a score percentage of 99% with very good qualifications. The test results from a small group of students obtained a score percentage of 98% with very good qualifications. Based on this, the e-module developed is valid and suitable for use in learning activities. The implication of this research is that teachers can use e-modules based on Balinese upakara ethnomathematics as a reference or special learning tool for grade 2 elementary school geometry material. Through the use of this e-module, students will gain new learning experiences. Apart from that, the use of technological developments and attractive visual, audio and video displays will accommodate students' learning styles, both auditory and visual learning styles.